Education advocacy for South Sudan: Lessons from Malala Yousafzai's 2014-2023 speeches - CONTESA, YENIS; Sahide, Ahmad (Faculty of Communications Science, Dr. Soetomo University, 2025)
Low access to education for women in South Sudan is caused by prolonged conflict, food crisis and lack of policy support. In this context, Malala Yousafzai's advocacy model inspires awareness of the importance of education for women. article explored the new advocacy model of education pioneered by Malala Yousafzai in South Sudan, based on her speeches from 2014 to 2023. The theoretical approach applied included the strategies of information politics, political symbols, political leverage, and accountability politics developed by Margareth E. Keck and Kathryn Sikkink. This research used a qualitative method with an in-depth literature review approach. This research uses NVivo 14 software, Anthiago.com, and the Critical Discourse Analysis (CDA) method for data analysis. Text data was collected through Anthiago.com, then transcribed to facilitate the analysis process. The CDA approach examined the discourse structure in Malala Yousafzai's speech, identifying the advocacy strategies applied. The results revealed that Malala's empowerment model effectively motivated young people and stakeholders in South Sudan to participate actively in educational initiatives. However, NGOs operating in the region face significant challenges that hinder the effectiveness of their advocacy programmes. This article also emphasises the importance of educational ethics as a foundation for women-focused education programmes in South Sudan. Thus, this article offers a new perspective in understanding the women's empowerment movement and education in South Sudan, inspired by the advocacy principles championed by Malala Yousafzai. Provide a brief description of the phenomenon raised in this research. Revised